2016
DOI: 10.1103/physreva.94.063628
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-broken states in a system of interacting bosons on a two-leg ladder with a uniform Abelian gauge field

Abstract: We study the quantum phases of bosons with repulsive contact interactions on a two-leg ladder in the presence of a uniform Abelian gauge field. The model realizes many interesting states, including Meissner phases, vortex fluids, vortex lattices, charge density waves, and the biased-ladder phase. Our work focuses on the subset of these states that breaks a discrete symmetry. We use density matrix renormalization group simulations to demonstrate the existence of three vortex-lattice states at different vortex d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 113 publications
(290 reference statements)
6
100
0
Order By: Relevance
“…In Ref. [56], an incommensurate Meissner phase has been observed numerically for density an 0 = 0.4 at flux aχ/(2π ) = 0.4, which belongs to the precursor-to-Laughlin state region on our phase diagram. The study in Ref.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In Ref. [56], an incommensurate Meissner phase has been observed numerically for density an 0 = 0.4 at flux aχ/(2π ) = 0.4, which belongs to the precursor-to-Laughlin state region on our phase diagram. The study in Ref.…”
Section: Discussionmentioning
confidence: 56%
“…Vortex lattice states, in which the discrete lattice translation symmetry is spontaneously broken, exist for U finite [55]. The two-leg ladder has other such symmetry broken states: charge density waves, as well as the biased ladder state which breaks the symmetry between the two chains [56].…”
Section: Model and Previous Resultsmentioning
confidence: 99%
“…Table I summarizes the weak and strong-coupling duality relations. In the weak coupling regime of bosonic ladders few VL superfluids were observed [3,4] to survive quantum fluctuations on top of the classical Josephson-junction (JJ) limit [5]. A vortex in the classical JJ limit, where the phase at each ladder site has definite value, carries a quantum of a fluxoid and is localized on …”
mentioning
confidence: 99%
“…simulations of a Bose-Hubbard model on a two-leg ladder with flux showed that particle densities get depleted in the plaquettes where vortices sit, when including quantum fluctuations, and topological excitations of the VL states are domain walls, carrying fractional fluxoids [3,4]. Contact-interacting cold quantum gases loaded in onedimensional lattices, with an additional second "synthetic" dimension, can explore this duality in the presence of a homogeneous gauge field.…”
mentioning
confidence: 99%
See 1 more Smart Citation